Energy prices, generators, and the (environmental) performance of manufacturing firms - Greve, Hannes,Kis-Katos, Krisztina,Renner, Sebastian (Verein für Socialpolitik, 2021)
Passing federal environmental policy reform is a challenge as the approval of interest groups such as consumers and state-level governments is often a prerequisite. Among others, the burden sharing's progressivity has a large impact on reform approval. We investigate how carbon tax payments by states to a federal authority are influenced by differences in technological emission intensity and wealth and show how they can turn out to be at the expense of poor states. We show that a uniform federal carbon tax that is endorsed by all states with equal per capita transfers can theoretically put a higher burden on poorer states than richer states. The opposite applies for transfers based on historical emissions (sovereignty transfers) which reduce the burden of emissionintensive states. We test our results numerically in a general equilibrium model with a vertical federalism governance structure calibrated to the European Union. Our simulations show that a federal minimum emissions tax with sovereignty transfers is twice as high as for equal per capita transfers and also has a progressive effect.Generator use is widespread among firms in developing and emerging economies, including Indonesia, shielding them from unreliable and insufficient electricity supply. This, however, makes these firms more vulnerable to fuel price increases, as well as more emission intensive. We exploit variation in policy-induced fossil fuel and electricity tariff adjustments using a rich panel data set of large manufacturing firms to estimate the impact of energy price increases on generator-reliant firms versus those not relying on generators. We find that generator-reliant firms reduce output and value added by around 0.6-0.8 percent in response to a ten percent fossil fuel price increase, and adjust inputs flexibly: Material input and labor demand fall by 0.7 and 0.5 percent, respectively. Because firms dis-adopt generator use in response to higher fuel prices, emission and energy intensity of production declines by around 0.7-0.8 percent on average. Electricity price increases, in contrast, are absorbed and do not lead to differential input adjustments in the short term. As firms that use generators also have a higher cost share of grid electricity, value added and labor productivity decline to a greater extent compared to other firms. In addition, rising electricity prices further incentivize inefficient generator use.
10419/242382
Keywords: Kongressbeitrag; Graue Literatur; energy prices; manufacturing sector; firm performance; emission intensity; generators